THE STATUS OF THE POPULATION'S USE OF THE STOCK MARKET IN UZBEKISTAN - Egamnazarova Gulnoza (Western European Studies, 2024)
The use of the population in the stock market, that is, the financial markets, in Uzbekistan is not popular. Large companies and organizations do not directly sell most of their shares and bonds. Financial literacy is one of the important factors that determine the level of correct and rational use of money by the population of the country. Financial literacy gives us the ability to control our money, manage various risks, protect our savings from various risks, and consider important factors when making investments.
Keywords: population; financial literacy; share; stock market